Psychological impact of COVID-19 restrictions among individuals at risk of exercise addiction and their socio-demographic correlates: a Saudi Arabian survey study - Syed, Nabeel Kashan; Alqahtani, Saad; Meraya, Abdulkarim M.; Elnaem, Mohamed Hassan Abdelaziz; Albarraq, Ahmed A.; Syed, Mamoon H.; Ahmed, Rayan A.; Griffiths, Mark (Springer Nature, 2022)
Exercise addiction (EA) has been described as a condition of psychological dysfunction characterized by excessive and obsessive exercise patterns, show withdrawal symptoms when unable to exercise, and experience numerous conflicts and other negative consequences in their social and professional lives, due to the extremely high volumes of exercise. The main objective of the present study was to assess the risk of exercise addiction among a Saudi Arabian sample of regular exercisers and to investigate possible associations between their inability to exercise during the COVID-19 pandemic lockdown (due to the closure of public gyms, swimming pools, and health clubs) and depression, anxiety, and loneliness. A total of 388 regular-exercising Saudis participated in an online cross-sectional survey over three months (December to February 2021). The study sample comprised 89.9% (males) and 10.1% (females), with a mean age of 28.59 years (SD ± 6.69). A 36-item online self-report survey was used for data collection. The prevalence of being at risk of exercise addiction among participants of the present study was 13.1%. Positive significant associations were noted between risk of exercise addiction and depression (r = .41; p < .01), risk of exercise addiction and anxiety (r = .20; p < .01), and risk of exercise addiction and loneliness (r = .17; p < .01). The findings of the present study suggest that those individuals at risk of exercise addiction might also be at an elevated risk of developing negative psychological impact owing to the disruption of the amount of exercise engaged in due to COVID-19 pandemic-related restrictions and therefore these high-risk individuals should receive appropriate psychological support to help them overcome the negative impact of the ongoing pandemic.